Method for analysing the user experience in MOOC platforms - Pascual Espada, Jordán; Castillo Rodríguez, Cristina; García Díaz, Vicente; González-Crespo, Rubén (2014 International symposium on computers in education (SIIE), 2020)
MOOCs have recently become very popular, since some of these massive online courses can reach thousand students. Faculty members from top universities deliver courses through MOOC platforms: Coursera, Edx, Miriada X, etc. Apart from the content, many other factors can influence the quality of a course; for instance, a bad user experience of a Web MOOC platform can lead students to drop out an interesting and well-organised course. MOOC platforms require much effort to care for the user experience. This research aims to develop a specific method for evaluating the user experience of MOOC platforms. The method is based on the general principles of Web user experience and highlights the aspects influencing MOOCs. The system proposed in this paper calculates a quantifiable index, useful for comparing different MOOC platforms, quantifying the quality evolution of the user experience, and promoting further studies so as to determine the impact of the user experience on students: satisfaction in surveys, enrollment figures, dropout rates, among others.
.
Keywords: MOOC; e-learning; user experience; evaluation systems; WOS(2); Scopus(2)